ANALISIS KESULITAN PEMAHAMAN MEMBACA PADA MAHASISWA ANGKATAN 2015 PENDIDIKAN BAHASA MANDARIN UNIVERSITAS TANJUNGPURA - Maulidiana Maulidiana; Ina Ina; Suhardi Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractReading lesson is one of the important lesson in Mandarin class. Some people consider reading lesson is difficult lesson, because when learning process they often found difficulties. To know the difficulties in learning reading Mandarin Language, the authors do research for Mandarin students of Mandarin Language Education Tanjungpura University 2015. In the research process, the author use questionnaire and test methods. The questionnaire was given with aim to find out reason students reading difficulties and test were given in order to know the level of student reading comprehension. After do research, author conclude that the most dominant difficulties in reading are not knowing the meaning of the words, not knowing the letters, the comlexity of grammar and also the difficulty of understanding the reading content. This research indicate that the result of reading comprehension level on students of class A Mandarin Language Education Program 2015 is less and class B is good. Keywords: Analysis, Difficulty, Reading Comprehension